2005
DOI: 10.1002/cphc.200400546
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of [D2]Methanol on Ru(001)O Surfaces: The Influence of Preadsorbed Oxygen on the Methoxide Geometry

Abstract: The influence of oxygen precoverage on the bonding geometry of methoxide on Ru(001) was studied using the isotopically labeled molecule CHD2OH by reflection-absorption infrared spectroscopy (RAIRS). This molecule is an excellent model because the vibrational spectra of CHD2O- may be unambiguously correlated with the adsorption configuration. For Ru(001)--O layers with an effective oxygen coverage (theta0) between 0.25 and 0.6 ML (ML=monolayer), the influence of the oxygen precoverage was shown to vary with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Bands at 1700−1600 cm -1 in CH 3 OH, CH 2 DOH, and CH 3 OD are noise. b Bands were assigned on the basis of literature values. c Values are normalized to the CO streching mode in CH 3 OH at 1043.6 cm -1 . d Band positions and integrated area absorbance (relative integrated band strength) were obtained by the least-square method (peak deconvolution).…”
Section: Methodsmentioning
confidence: 99%
“…Bands at 1700−1600 cm -1 in CH 3 OH, CH 2 DOH, and CH 3 OD are noise. b Bands were assigned on the basis of literature values. c Values are normalized to the CO streching mode in CH 3 OH at 1043.6 cm -1 . d Band positions and integrated area absorbance (relative integrated band strength) were obtained by the least-square method (peak deconvolution).…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22][23][24] To achieve rational modi-cation on the anode catalysts, many efforts have been devoted to understanding the CH 3 OH oxidation mechanism on Ru catalysts experimentally. Unfortunately, although these studies were performed by using the same infrared absorption spectroscopy, conicting evidence on adsorption and the reaction mechanism of CH 3 OH oxidation have been observed on clean 16,17 and O-precovered 25,26 Ru(0001) surfaces. For the adsorption of reaction intermediates, Barros et al 17 found upright and tilted methoxy (CH 3 O) and formaldehyde (CH 2 O); while Gazdzicki et al 19 proposed an upright conguration of CH 3 O.…”
Section: Introductionmentioning
confidence: 99%